National Anti-corruption strategies in the system of prevention of corruption of Ukraine - Hrechaniuk, Roksolana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2019)
In the article, based on the analysis of scientific as well as regulatory and legal sources, the scientific analysis of national anti-corruption strategies in the system of corruption prevention in Ukraine is made. It is noted that the issue of anti-corruption activity, regardless of its spheres of existence in modern legal science, is at the stage of discussion. The introduction of such an important tool as the Anti-Corruption Strategy at the level of the law is a testament to the state’s recognition of the existence of a corruption problem and the need to take measures to prevent and counteract this phenomenon. A comparative analysis of the strategies implemented in the past has revealed a partial implementation of these strategies, which instead speaks of gradual and systemic anti-corruption progress, which may not be as rapid as required by society, but is gradually integrating new anti-corruption practices into different spheres of life. The formulation of a new Anti-Corruption Strategy should take into account the opinion of the expert community, the public, international experts, as well as on the basis of terminological certainty, absolute assurance of observance of human rights and the rule of law, taking into account previous achievements and shortcomings. An anti-corruption strategy is a normative-oriented benchmark that is specified by a specific period of time, outlined by the problem and the projected result. However, this document is a declarative act of the state which does not foresee negative consequences for its non-implementation, which causes its neglect or improper implementation. Therefore, it is necessary to provide for safeguards for its proper implementation, including accountability measures, and to define mechanisms for proper control in this area when formulating the Anti-Corruption Strategy. Forming an anti-corruption strategy is not identical to forming an anti-corruption policy, since the latter is a broader category and, among other things, involves the creation of strategic documents and mechanisms for their implementation. Anti-corruption policy should be considered as a set of established and normative mechanisms, tools and methods aimed at ensuring public interest caused by the need to reduce the phenomenon of corruption through the use of instruments of prevention, counteraction, and accountability. In this case, the Anti-Corruption Strategy is one element of the formalization of anti-corruption policy, which in turn is important, and to some extent, crucial.